Studies on Kinetics of Hydroxylation of p-Rosaniline Hydrochloride by Sodium Hydroxide in Micellar Environment - KOTHWALA, D.M.; PATEL, M.S.; NAGAR, T.N. (Asian Journal of Chemistry, 2010)
Basic hydrolysis of p-rosaniline hydrochloride in presence of solution of anionic surfactant, e.g., sodium dodecyl sulphate (SDS), cationic surfactant, e.g., hexadecyl trimethyl ammonium bromide (C16TABr) and nonionic surfactant, e.g., triton X-100 has been studied. C16TABr is known to increase the rate of reaction of triphenyl metIiyl carbonium ions with the hydroxide ion, where as the anionic micelles of SDS and non-ionic of TX-100 inhibit this rate. At lower concentration of NaOH, reaction rate increase rapidly with cationic surfactant concentration and with increasing hydroxide ion concentration, an inhibition effect is observed for all surfactant concentrations studied. The addtion of monohydric alcohol, viz., ethanol, n-propanol, n-butanol and solvent like acetone and ethylene glycol decreases the cationic micellar catalysed rate of carbinol formation and on the other hand increase the anionic micellar inhibited rate. The effectiveness of these solvents in reducing the extent of overall inhibition by sodium dodecyl sulphate has been found to follow the order: ethylene glycol < n-propanol < n-butanol. These trends are discussed with reference to the probable factors that are responsible for the change in the reaction rate in the presence of organic solvents. The effect of polyethylene glycol has also been investigated in the presence of C16TABr. Effect of various salts, viz., KCI, KBr, KNO3, K2SO4 and NaCI has also been studied on this reaction.